2023
DOI: 10.1002/cam4.5792
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in stage at diagnosis among breast cancer molecular subtypes in China

Abstract: Background Disease stage at diagnosis and molecular subtypes are the main determinants of breast cancer treatment strategies and prognosis. We aimed at examining the disparities and factors associated with the stage at diagnosis among the molecular subtypes in breast cancer patients in China. Methods We identified patients with first primary breast cancer diagnosed between January 1, 2016, and December 31, 2017, from 23 hospitals in 12 provinces in China. We analyzed the proportion of non‐early‐stage (stages I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In contrast, in developing countries only 20 -60% of patients are diagnosed at earlier stages, while a higher percentage, ranging from 30% to 80%, are diagnosed at stages III and IV [25] . According to some studies in China [4,30,35] have also shown that between 60 -70% of the patients are diagnosed in stage I and II. However, the 5-year survival rate for Chinese women with breast cancer from 2010 to 2014 was only 83.2% [1] .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in developing countries only 20 -60% of patients are diagnosed at earlier stages, while a higher percentage, ranging from 30% to 80%, are diagnosed at stages III and IV [25] . According to some studies in China [4,30,35] have also shown that between 60 -70% of the patients are diagnosed in stage I and II. However, the 5-year survival rate for Chinese women with breast cancer from 2010 to 2014 was only 83.2% [1] .…”
Section: Discussionmentioning
confidence: 99%